Criteria Associated with Treatment Decisions in Juvenile Idiopathic Arthritis with a Focus on Ultrasonography: Results from the JIRECHO Cohort - Sara Baydoun; Sandrine Jousse-Joulin; Alain Saraux; Perrine Dusser-Benesty; Charlotte Borocco; Caroline Galeotti; Annette Von Scheven; Michael Hofer; Brigitte Bader-Meunier; Florence Aeschlimann; Sylvain Breton; Laetitia Sparsa; et al. (Rheumatology and Therapy, 2022)
Abstract Background The treatment of children with juvenile idiopathic arthritis (JIA) to prevent disability is a major challenge in paediatric rheumatology. The presence of synovitis, which is difficult to detect in children, is associated with structural damage. Musculoskeletal ultrasonography (MSUS) can be used in patients with JIA to reveal subclinical synovitis. Objective The primary aim was to determine whether the use of MSUS was associated with therapeutic modification in patients with JIA. The secondary aim was to identify other factors associated with therapeutic decisions. Methods We conducted an observational study based on the JIRECHO multi-centre cohort, which was developed to provide a systematic MSUS follow-up for patients with JIA. Follow-up occurred every 6 months and included clinical and MSUS examinations. We included children who underwent MSUS of the elbows, wrists, second metacarpophalangeal joints, knees and ankles, which was performed by expert sonographers. Clinical and biological data, disease activity scores and information on therapeutics were collected. Results A total of 185 visits concerning 112 patients were recorded. Three groups were defined according to the therapeutic decision: escalation (22%, n = 40), de-escalation (14%, n = 26) or stable (64%, n = 119). In the “therapeutic escalation” group: the presence of ultrasonographic synovitis in B-mode and the presence of grade 2 or 3 synovitis in B-mode were not significantly more frequent than in the “stable therapeutic or de-escalation” group (80% versus 65%, p = 0.06; 33% versus 19%, p = 0.06), and the patient’s and physician’s visual analogue scale (VAS) scores, the clinical JADAS and the C-reactive protein level were significantly higher, but only physician’s VAS score remained in the model of logistic regression. In the “therapeutic de-escalation” group: there was no difference in the presence of US synovitis compared with the “stable therapeutic or escalation” group (62% versus 69%, p = 0.48). Conclusion Even though US synovitis tended to be more frequent in patients with therapeutic escalation, the study did not show that the presence of synovitis in MSUS was statistically associated with therapeutic modifications in patients with JIA. Treatment remained stable despite the presence of US synovitis.